MOBILE APLIKASI BERBASIS ANDROID UNTUK SISTEM INFORMASI MONITORING PELANGGARAN SISWA PADA SMA NEGERI 1 GORONTALO - Idris, Nur Oktavin; Farid, F.; Aer, Rahmawaty Anestasya (Journal Of Software Engineering And Communication, 2023)
The problem in the process of monitoring student violations at SMA Negeri 1 Gorontalo is accumulating violation points for each student because they have to look for data one by one in the archives cupboard so that monitoring violations and presenting information on student violations to parents of students is not optimal because student violation points can only be conveyed periodically in semesters to students and parents of students, as a result, parents find it difficult to get information on the progress of their children quickly. This study aims to design an Android-based Student Violation Monitoring Information System at SMA Negeri 1 Gorontalo which can facilitate counseling teachers in managing student violation points data and make it easier for parents to obtain information on student points and violations via smartphone. The system analysis method used is the Research and Development method. The application is built with Java and PHP programming languages and MySQL database as data storage. The system uses web service techniques to retrieve data from the server. The results of this study obtained the final result in the form of an Android-based information system at SMA Negeri 1 Gorontalo which can help as a medium for conveying information on student violations along with the points obtained, equipped with a notification feature and also output a warning letter in pdf format. The tests were carried out using a black box which resulted in the suitability of the functions of the events in the application as well as. The system implementation is applied to Android version 11.0, version 10.0 (Q), and Version 9.0 (Pie). The minimum system limitation on the Android application is Android version 8.0 (Oreo).